Influence of Celebrity Endorsement on Purchase Decision-making - Hapsari, Elvira Dwi (APPS Publications, 2022)
ABSTRACT Objective – This study aims to determine the effect of trustworthiness, attractiveness, and expertise possessed by celebrity endorsers on consumer purchase decision-making and to determine the effect of trustworthiness, attractiveness, and expertise that celebrity endorsers have on the buying interest of Instagram social media users partially. Methodology – The stratified random sample approach was used to determine respondents’ responses to each variable in this study. Data was obtained through a questionnaire method for 50 respondents who frequently watch celebrities endorsing products or services. The data is then analyzed using quantitative analysis, which includes validity and reliability, as well as the F and T tests to prove the hypothesis. Multiple linear regression analysis is the data analysis technique used to see the effect. Findings – Celebrity attractiveness influences purchase decision-making; however, trustworthiness and expertise do not. Novelty – This is one of the first studies to examine the relationships between attractiveness, trustworthiness and expertise and purchase decision-making. Keywords: celebrity endorsement, attractiveness, trustworthiness, expertise, decision-making